Pulse‐Administered Toceranib Phosphate Plus Lomustine for Treatment of Unresectable Mast Cell Tumors in Dogs. (25th June 2015) - Burton, J.H.; Venable, R.O.; Vail, D.M.; Williams, L.E.; Clifford, C.A.; Axiak‐Bechtel, S.M.; Avery, A.C.; Thamm, D.H.
<x xml:space="preserve">Abstract</x> Background Nonresectable mast cell tumors (MCT) in dogs remain a therapeutic challenge, and investigation of novel combination therapies is warranted. Intermittent administration of tyrosine kinase inhibitors (TKI) combined with cytotoxic chemotherapy may effectively chemosensitize canine MCT while decreasing cost and adverse effects associated with either agent administered as monotherapy. Hypothesis/Objectives The primary study objectives were to (1) identify the maximally tolerated dose (MTD), (2) determine the objective response rate (ORR) and (3) describe the adverse event profile of pulse‐administered toceranib phosphate (TOC) combined with lomustine. Animals Forty‐seven client‐owned dogs with measurable MCT. Methods Toceranib phosphate was given PO on days 1, 3 and 5 of a 21‐day cycle at a target dosage of 2.75 mg/kg. Lomustine was given PO on day 3 of each cycle at a starting dosage of 50 mg/m2. All dogs were concurrently treated with diphenhydramine, omeprazole, and prednisone. Results The MTD of lomustine was established at 50 mg/m2 when combined with pulse‐administered TOC; the dose‐limiting toxicity was neutropenia. Forty‐one dogs treated at the MTD were evaluable for outcome assessment. The ORR was 46% (4 complete response, 15 partial response) and the overall median progression‐free survival (PFS) was 53 days (1 to >752 days). On multivariate analysis, variables significantly associated with improved PFS included response to treatment, absence of metastasis, and no previous chemotherapy. Conclusions and clinical importance Combined treatment with pulse‐administered TOC and lomustine generally is well tolerated and may be a reasonable treatment option for dogs with unresectable or metastatic MCT.